Synthetic routes of the reduced graphene oxide - Feng, Jianlang; Ye, Yunqing; Xiao, Meng; Wu, Gang; Ke, Yu (Chemical papers, 2020)
Graphene has attracted great attention owing to its exceptional electrical, mechanical, optical, thermal and antimicrobial properties. Graphene oxide (GO) and reduced graphene oxide (rGO) are two important derivatives of graphene, and the latter can be achieved through the reduction reaction of GO. Many methods including reductant reduction, irradiation reduction, electrochemical reduction and microbial reduction were summarized systematically, with an aim at obtaining superior rGO and even rGO-based devices on a large-scale production. The latest development of different strategies on the reduction of GO and their relevant mechanism were reviewed as a guide for further studies of rGO.